Pertamina’s corporate strategy - action plan to 2025 - Hoang Thi Dao; Dao Minh Phuong; Hoang Thi Phuong (Petrovietnam Journal, 2020)
Transformation from an oil company to an energy company is currently a trend for several major oil companies, in response to the situation where fossil fuels are gradually exhausting as well as to develop new and clean energy to protect the environment. Indonesia’s PT Pertamina (Persero) is not out of the trend. Recently, it has transformed into an energy company, with the vision of becoming a world-class one by 2025. The article introduces the corporate strategy and strategic plan of Pertamina until 2025. Specifically, Pertamina focuses on: (i) improving oil and gas reserves and exploiting geothermal energy; (ii) vigorously upgrading and expanding existing refineries and investing in new refineries to increase production and enhance product quality; (iii) increasing the share of new and renewable energy in Indonesia’s energy mix.